ANALISA KELUHAN MUSCULOSKELETAL PADA POSTUR TUBUH PEKERJA PENYERUT KAYU DI MEBEL UD. SETIA USAHA DENGAN MENGGUNAKAN METODE RAPID UPPER LIMB ASSESSMENT - Apriyadi Salsa; Subchan Asy'ari (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2020)
UD.Setia Usaha a business in the field of furniture, during the production process, starting from the activity of the initial raw materials to the process of finished products there is a position that causes interference with the muscular system and needs to improve working posture. Bent position, working with standing, back bent, excessive workload are activities that need to be evaluated gradually. The position of the furniture worker UD. Faithful Business that is not ergonomic. can cause musculoskeletal disorder (MSDs). The purpose of this study was to determine the worker's posture on the activities of furniture workers in the wood shavers at UD. Faithful Business Data collection is done by direct observation to the field and interviews. The data obtained were analyzed using the RULA method, then the grand score was categorized based on the action level of the RULA. The result is the final score of each work posture and level of risk. There are 2 work postures that are often performed by workers. Work posture has a final score of 7 and a higher level of risk is to stand bent and arms outstretched.